(untitled) (Journal of Oriental Studies, 2016)
In given article the nature from an ethnolinguistic position connected with money reveals, i.e. with richness, the basic sources of richness (gold, tenge, tiyin, fels, etc.) proverbs-sayings in the Kazakh and Turkish languages, are considered their difference and similarity among themselves.